Technology Exposure: Its Relationship to the Study Habits and Academic Performance of Students - Berondo, Ronilo G.; Dela Fuente, Jayson A. (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2021)
The 21st century emphasizes the role of technology in different facets of life, especially in the educational system, as it serves as a platform for teachers and students in the delivery of effective teaching and learning process. In this perspective, descriptive-correlational research determines the level of technology exposure and its relationship to the study and academic performance in Social Studies subject of the one hundred seventy-four (174) students who were randomly chosen from a total population of six hundred eighty-eight (688) during the School Year 2018-2019 in the three selected public secondary schools in the district of Tapaz West, Schools Division of Capiz, Philippines. The data were gathered using a standardized survey questionnaire and analyzed using descriptive statistics: mean, percentage, frequency count, and standard deviation. For the inferential statistics: t-test, analysis of variance, and Pearson r correlation at 0.05 level of significance through the aid of the SPSS software version 27. The study's significant findings revealed that exposure to technology significantly relates to students' study habits. At the same time, it does not significantly relate to their academic performance in Social Studies subjects. The findings suggest that school administrators, parents, teachers, and other stakeholders should ensure that students are properly guided to the right technology platforms to support learning and improve their study habits towards excellent academic achievement.